2014
DOI: 10.3201/eid2009.140418
|View full text |Cite
|
Sign up to set email alerts
|

Pork Consumption and Seroprevalence of Hepatitis E Virus,Thailand, 2007–2008

Abstract: The nationwide seroprevalence of hepatitis E IgG was determined among young men in Thailand. Overall seroprevalence was 14% (95% CI 13%–15%); range by province was 3%–26%. Seroprevalence was lowest in the south, an area predominantly occupied by persons of the Islam religion, whose dietary laws proscribe pork.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 9 publications
0
25
2
Order By: Relevance
“…With an IgG seroprevalence of 51.8%, HEV is hyperendemic in the rural population at least in Vientiane Capital. In South‐East Asia, seroprevalence rates between 8.9% and 77.7% have been reported (Gonwong et al, ; Holt et al, ; Sa‐nguanmoo et al, ; Yamada et al, ). This wide range certainly reflects regional differences and differing cohort selection criteria, but also disparities in sensitivity and specificity between commercial antibody detection kits (Avellon, Morago, Garcia‐Galera del Carmen, Munoz, & Echevarria, ; Vollmer, Diekmann, Eberhardt, Knabbe, & Dreier, ; Wenzel, Preiss, Schemmerer, Huber, & Jilg, ).…”
Section: Discussionmentioning
confidence: 99%
“…With an IgG seroprevalence of 51.8%, HEV is hyperendemic in the rural population at least in Vientiane Capital. In South‐East Asia, seroprevalence rates between 8.9% and 77.7% have been reported (Gonwong et al, ; Holt et al, ; Sa‐nguanmoo et al, ; Yamada et al, ). This wide range certainly reflects regional differences and differing cohort selection criteria, but also disparities in sensitivity and specificity between commercial antibody detection kits (Avellon, Morago, Garcia‐Galera del Carmen, Munoz, & Echevarria, ; Vollmer, Diekmann, Eberhardt, Knabbe, & Dreier, ; Wenzel, Preiss, Schemmerer, Huber, & Jilg, ).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Seroprevalence studies in Thailand further confirmed a link between dietary or occupational exposure to swine and the presence of HEV immunity. 13,14 The frequency of HEV detection in pork and variety meats sold in Thai markets was similar to or lower than the prevalence found in industrialized countries. [15][16][17] In several countries, inadvertent HEV transmission to blood recipients was associated with blood donation from healthy donors who may have acquired zoonotic foodborne HEV infection.…”
mentioning
confidence: 55%
“…14 Nationwide, approximately 14% of Thai men in their 20s possessed anti-HEV IgG antibodies. 13 Thus, past exposure to HEV in Thailand as measured by HEV seroprevalence does not differ drastically from the rates found in western Europe. [42][43][44] Data regarding the prevalence of HEV in healthy adults have important implications in ensuring the safety of donated blood.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations